(untitled) (Fiep Bulletin - online, 2013)
Brazil is a country of waters, there are beaches, lagoons, rivers and in all of these the local inhabitants must be capable of interacting and surviving in the aquatic surroundings. The project NATAÇÃO NO MAR (SWIMMING IN THE SEA) began in 2005 in Rio das Ostras - Rio de Janeiro, with the purpose of teaching swimming and lifesaving techniques, enabling the participants to prevent the accidents that are usual when dealing with water. The professionals of project NATAÇÃO NO MAR have for the past two years been developing and improving a methodology that encompasses the different techniques that must be used when teaching and improving swimming skills in the sea environment as well as the aspects that serve to achieve social inclusion and integration. Methodology: For a clearer understanding of the project we will summarize its history, the teaching methodology used and the activities carried out in the project, following which we will show an analysis of the research results. The social (Rivermead) scale will be used as well as a questionnaire developed by the professionals of the project so as to rate the changes in habit and attitudes towards health and other aspects. Results: The data from the research that used the Rivermead social scale as an instrument, shows a great change in the life of the pupils in the project and their families. The data from both researches carried out based on the questionnaires made up by the project’s professionals shows ample acceptance regarding the activities organized by the group as well as a remarkable change in the habits of the pupils regarding the environment.